1970
DOI: 10.1159/000175273
|View full text |Cite
|
Sign up to set email alerts
|

Some Metabolic Effects of Dietary Sucrose

Abstract: (1) Male, weanling rats were fed on diets containing 60% sucrose or 60% starch and the liver and adipose tissue were examined in vitro for their ability to oxidise glucose and to synthesise fat from glucose, using radioactive glucose as an indicator. (2) Compared with the livers of rats fed on starch those fed on sucrose showed a severe depression of both glucose oxidation and lipogenesis. When two forms of radioactive glucose were used, labelled in carbon-1 or universally labelled, the change in proportions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
1

Year Published

1971
1971
1988
1988

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…This is at variance with findings of Bruckdorfer et al (5) who found a lower serum insulin concentration in rats fed fructose or sucrose diets than in rats on glucose, maltose or starch diets. These different findings may be, among other reasons, caused by the use of different strains of rats; strain differ ences are known to modify the metabolic effect of dietary fructose or sucrose in the rat (2). In other experiments (26), we did not find any differences in the basal serum insulin level between groups on the starch or sucrose diet.…”
Section: Discussioncontrasting
confidence: 63%
“…This is at variance with findings of Bruckdorfer et al (5) who found a lower serum insulin concentration in rats fed fructose or sucrose diets than in rats on glucose, maltose or starch diets. These different findings may be, among other reasons, caused by the use of different strains of rats; strain differ ences are known to modify the metabolic effect of dietary fructose or sucrose in the rat (2). In other experiments (26), we did not find any differences in the basal serum insulin level between groups on the starch or sucrose diet.…”
Section: Discussioncontrasting
confidence: 63%
“…There are many reports of changes in various metabolic and physiological parameters following the replacement of dietary starch by sucrose or fructose (4). In most experiments the sugars were fed at high levels of 60-80 % of the diet and results observed for relatively short periods of time.…”
mentioning
confidence: 99%
“…Recent investigations revealed that the substitution of starch in the diet by sucrose leads in the rat to a reduced lipid synthesis in adipose tissue and a reduced insulin sensitivity of adipose tissue [2,4,[23][24][25]. Nutritional deficiencies of choline or of trivalent chromium which could be considered the possible cause of sucrose-induced inhibition were ruled out [26].…”
mentioning
confidence: 99%